THE EFFECT OF INTERNET USAGE TOWARDS THE LEARNING INTEREST OF STUDENTS OF ACCOUNTING DEPARTMENT AT MARANATHA CHRISTIAN UNIVERSITY BANDUNG - Vinny Stephanie Hidayat; Debbianita Debbianita (COMPETITIVE, 2019)
The aim of this research is to determine the effect of Internet Usage (using internet access) towards the Learning Interest of Students at Maranatha Christian University. The population of this research is whole of the accounting students of Maranatha Christian University. The sample of this research is 100 accounting students of Maranatha Christian University. The method used in this research was explanatory research, and the sampling method used was judgement sampling method. Research hypothesis testing using T test, F test, and multiple regression analysis using SPSS version 20.0. The result of this research shows that internet usage affect the student’s interest in studying, Thus, the hypothesis of this research is empirically supported.Keywords: Internet Usage, Interest of Studying, Internet Access